2016
DOI: 10.4238/gmr15048967
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin mRNA expression and its association with body weight and carcass traits in Yunnan Wuding chicken

Abstract: Myostatin (MSTN) is expressed in the myotome and developing skeletal muscles, and acts to regulate the number of muscle fibers. Wuding chicken large body, developed muscle, high disease resistance, and tender, delicious meat, and are not selected for fast growth. Broiler chickens (Avian broiler) are selected for fast growth and have a large body size and high muscle mass. Here, 240 one-day-old chickens (120 Wuding chickens and 120 broilers) were examined. Twenty chickens from each breed were sacrificed at days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Among the DEGs involved in growth and development identified in this study, some were previously reported to be closely related to muscle growth and development. As a regulator of skeletal muscle growth, MSTN plays a key role in negatively regulating the growth and development of skeletal muscle and influencing the strength and quality of muscles (Yi et al, 2016;Liu et al, 2016;Rao et al, 2016). MSTN can inhibit the activation, proliferation, and differentiation of myogenic satellite cells (McFarland et al, 2006), and delayed differentiation of myoblasts due to a lack of MSTN results in significant changes in the morphology of myoblasts (Sato et al, 2006), which indicates that MSTN plays an important role in chicken embryogenesis and skeletal muscle development and is one of the important factors regulating muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…Among the DEGs involved in growth and development identified in this study, some were previously reported to be closely related to muscle growth and development. As a regulator of skeletal muscle growth, MSTN plays a key role in negatively regulating the growth and development of skeletal muscle and influencing the strength and quality of muscles (Yi et al, 2016;Liu et al, 2016;Rao et al, 2016). MSTN can inhibit the activation, proliferation, and differentiation of myogenic satellite cells (McFarland et al, 2006), and delayed differentiation of myoblasts due to a lack of MSTN results in significant changes in the morphology of myoblasts (Sato et al, 2006), which indicates that MSTN plays an important role in chicken embryogenesis and skeletal muscle development and is one of the important factors regulating muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MSTN was regulated development of muscle fiber (Liu et al 2016). Liu et al (2016) exhibited that mRNA level of MSTN in breast muscle was lower in Wuding chicken than in broilers before 30 day. In contrast, after 30day, themRNA level was higher in breast muscle of Wuding chicken more than in broilers.…”
Section: Gene Expressionmentioning
confidence: 94%
“…Myostatin prevents proliferation of myoblast (Bass et al 1999) by inhibiting their cell cycle progression from the G1 to the S phase (Thomas et al 2000). Liu et al (2016) reported that the MSTN gene may be useful in molecular breeding in chicken owing to its negative regulatory effect on muscle mass.In chicken, Kocamis and Killefer (2002) showed that MSTN gene expression is increased in skeletal muscles during the second half of embryonic development and decline on hatching day. Furthermore, it lower expression in muscle of 30-day-old (Liu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of broilers is generally influenced by environment and heredity, and nowadays, under the condition of industrialized production, the most important factor affecting the growth of broilers is heredity. Growth trait is a quantitative trait regulated by multiple genes (Goto et al, 2019), such as myogenic regulatory factors (MRFs) (Zhu et al, 2016), insulin like growth factor 1/insulin like growth factor 1 receptor (IGF-I/IGF-IR) (Roelfsema et al, 2018), myostatin (MSTN) (Liu et al, 2016), etc. Therefore, it is necessary to study the molecular mechanism of growth regulation in poultry.…”
Section: Introductionmentioning
confidence: 99%